Annual Plan 2004-2005 Draft Proposals Government of Meghalaya - Planning Commission (Planning Commission, 2004)
Meghalaya was first created as an Autonomous Slate within the State of Assam on the 2,,d April, 1970 with the two erstwhile Districts of Assam, viz: the United Khasi & Jaintia Hills District and the Garo Hills District. The Autonomous State was upgraded into a full fledged State with effect from the 21s1 January, 1972. The State has a geographical area of 22,429 Sq.Kms approximately and has now 7 Districts viz : (i) the East Khasi Hills District (ii) the West Khasi Hilfs District (iii) the Jaintia Hills District (iv) the Ri-Bhoi District (v) the West Garo Hills District (vi) the East Garo Hills District and (vii) the South Garo Hills District. At the beginning, the State has 24 C&RD Blocks but the number has increased to 39 by the end of 2001-2002.
Planning Department Government of Meghalaya